"We're All in the Same Boat": A Review of the Benefits of Dragon Boat Racing for Women Living with Breast Cancer. (28th June 2012) - Harris, Susan R.
Abstract : This narrative review summarizes findings from quantitative and qualitative research literature that has been published over the past 15 years since an initial, community-based pilot study first challenged the long-held medical belief that vigorous, upper-body exercise would lead to lymphedema in women who were at risk due to treatments for breast cancer. Dragon boat racing originated in China more than 2000 years ago and has become a popular recreational and competitive support around the world. From the advent of the world's first breast cancer survivor dragon boat team, Abreast in a Boat launched in Vancouver, British Columbia, in 1996, there are now more than 140 breast cancer survivor dragon boat teams paddling and competing in 12 different countries. The wealth of quantitative and qualitative research that has ensued since that pilot study further supports the initial hypothesis that resistance exercise, for example, dragon boat paddling, is not only safe for women recovering from conventional breast cancer therapies but also shows that dragon boating has been embraced as a complementary exercise therapy by the cancer survivors participating in this magical sport.